Andrographolide promote the growth and immunity of Litopenaeus vannamei, and protects shrimps against Vibrio alginolyticus by regulating inflammation and apoptosis via a ROS-JNK dependent pathway - Yin, Xiaoli; Zhuang, Xueqi; Luo, Weitao; Liao, Meiqiu; Huang, Lin; Cui, Qiqian; Huang, Jiayi; Yan, Chunxia; Jiang, Zixiang; Liu, Yuan; Wang, Weina (Frontiers in Immunology, 2022)
Vibrio alginolyticus (V. alginolyticus) is one of the major pathogens causing mass mortality of shrimps worldwide, affecting energy metabolism, immune response and development of shrimps. In the context of the prohibition of antibiotics, it is necessary to develop a drug that can protect shrimp from V. alginolyticus. Andrographolide (hereinafter called Andr), a traditional drug used in Chinese medicine, which possesses diverse biological effects including anti-bacteria, antioxidant, immune regulation. In this study, we investigated the effect of Andr on growth, immunity, and resistance to V. alginolyticus infection of Litopenaeus vannamei (L. vannamei) and elucidate the underlying molecular mechanisms. Four diets were formulated by adding Andr at the dosage of 0 g/kg (Control), 0.5 g/kg, 1 g/kg, and 2 g/kg in the basal diet, respectively. Each diet was randomly fed to one group with three replicates of shrimps in a 4-week feeding trial. The results showed that dietary Andr improved the growth performance and non-specific immune function of shrimps. L. vannamei fed with Andr diets showed lower mortality after being challenged by V. alginolyticus. After 6 h of V. alginolyticus infection, reactive oxygen species (ROS) production, tissue injury, apoptosis, expression of inflammatory factors (IL-1 β and TNFα) and apoptosis-related genes (Bax, caspase3 and p53) were increased in hemocytes and hepatopancreas, while feeding diet with 0.5 g/kg Andr could inhibit the increase. Considering that JNK are important mediators of apoptosis, we examined the influence of Andr on JNK activity during V. alginolyticus infection. We found that Andr inhibited JNK activation induced by V. alginolyticus infection on L. vannamei. The ROS scavenger N-acetyl-l-cysteine (NAC) suppressed V. alginolyticus-induced inflammation and apoptosis, suggesting that ROS play an important role in V. alginolyticus-induced inflammation and apoptosis. Treated cells with JNK specific activator anisomycin, the inflammation and apoptosis inhibited by Andr were counteracted. Collectively, Andr promote the growth and immunity of L. vannamei, and protects shrimps against V. alginolyticus by regulating inflammation and apoptosis via a ROS-JNK dependent pathway. These results improve the understanding of the pathogenesis of V. alginolyticus infection and provide clues to the development of effective drugs against V. alginolyticus.